Dramaturgia hipertextual: ensayando la frontera - Galicia, Rocío (Latin American Theatre Review, 2011)
Departing from the theoretical concept of hypertextual theatre espoused by playwright,critic, and scholar Enrique Mijares, this essay describes the singular characteristicsthat grant a sense of unity to the hundreds of plays that have been written in the northern partof Mexico since the mid-90s in response to a reality that defies conventional dramatic representation.Taking examples from plays by Jesús González Dávila, Víctor Hugo Rascón Banda,Virginia Hernández, Medardo Treviño, and Enrique Mijares, among others, Galicia confirmsa new conceptualization of theatre that breaks away from linearity and binary oppositions. Inresponse to and under the influence of constant changes in science and technology, the Teatrodel Norte resorts to such techniques as intertextuality, hyperlinks, videoclips, multi-facetedcharacters, polysemy, and fragmentation to convey the disorder and instability that reignsthroughout the region. (JEB, article in Spanish)